Alteration of Testosterone Levels Changes Brain Wave Activity Patterns and Induces Aggressive Behavior in Rats - Estumano, Daniel Pantoja; Ferreira, Luan Oliveira; Bezerra, Paulo Augusto Lima; da Silva, Maria Clara Pinheiro; Jardim, Giovanna Coutinho; Santos, George Francisco Souza; Gustavo, Kayo Silva; Mattos, Bruna Gerrits; Ramos, Jorge Amando Batista; Jóia de Mello, Vanessa; da Costa, Edmar Tavares; Lopes, Dielly Catrina Favacho; et al. (Frontiers in Endocrinology, 2019)
Testosterone is responsible for several changes in the brain, including behavioral and emotional responses, memory and cognition. Given this, we investigated changes in the brain wave profile caused by supplementation with exogenous testosterone in both castrated and non-castrated rats. We also investigated the serum testosterone levels, renal and hepatic function, and the lipid and behavioral profiles. We found changes in the spectral wave power in both groups (castrated and non-castrated animals) supplemented with exogenous testosterone, consistent with an aggressive/hostile profile. These changes were observed in the electrocorticographic evaluation associated with increased power in low-frequency (delta and theta) and high-frequency (beta and gamma) activity in the supplemented animals. The castrated animals presented a significant decrease of wave power in the alpha frequency. This correlated with a decrease of the performance of the animals in the elevated plus-maze evaluation, given that the alpha wave is linked to the execution and visualization of motor processes. In the behavioral evaluation, the castrated animals presented a reduced permanence time in the elevated-plus maze, although this was prevented by the supplementation of testosterone. Testosterone supplementation induced aggressive behavior in non-castrated animals, but not in castrated ones. Supplemented animals had significantly elevated serum testosterone levels, while their urea levels were significantly lower, but without clinical significance. Our data indicate that testosterone supplementation in non-castrated rats, but not in castrated ones, causes electrocorticographic changes that could be associated with more aggressive and hostile behavior, in addition to indicating a potential for personality disorder. However, further studies are required to elucidate the cellular and molecular changes caused by acute testosterone supplementation.